Membangun Kesadaran Siswa terhadap Dampak Psikologis Bullying melalui Literasi Sekolah di MI Nurul Jadid Bondowoso - Dwi Wahyuni; Surya Yudhisthira Suwito; Yustisia Ramadhani Hendratno; Lala Bunga Istian; Aulia Nur Maharani Putri; Arifa Nur Fadhilah; Kiki Ayu Lestari; Agung Nugroro Puspito; Arin Berliana Angrenani; Mailulah Ely Fauziyah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This community service activity aims to build students' awareness of the psychological impact of bullying through a school literacy approach at MI Nurul Jadid Bondowoso. The main problem is the low level of student understanding regarding the forms and impacts of bullying, which are often considered normal. The program was carried out by seven students through three meetings on September 20, October 4, and October 19, 2025, using a participatory literacy approach involving discussions, video analysis, mini-dramas, and reflections. Evaluation results showed a 91% increase in student understanding based on a comparison of pre-test and post-test results. The activity concluded with the distribution of snacks and an educational trip to the lake behind the school as a means of applying the values of empathy and togetherness. Teachers responded positively as the activity helped students understand the dangers of bullying and fostered an attitude of mutual respect. The program succeeded in changing student behavior to become more caring and is expected to create a school environment free from bullying.